Extreme precipitation during the warm growing season amplifies methane emissions and reduces non-growing season contributions in a Tibetan alpine peatland - Zhenrong Lin; Zhirang Wu; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; Shaoying Wang; Xianhong Meng; Ruijun Long; Lei Ma (Agricultural and Forest Meteorology, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Pose estimation-guided CNN for tea bud detection and plucking point identification - Zhiye Shen; Jiang Yu; Yinghu Cai; Jinpeng Yang; Ping Chen; Weile Ruan; Wenbin Zhen; Ruijun Ma; Long Qi (Computers and Electronics in Agriculture, 2026)

Comprehensive characterization and evaluation of coupled LID system responses to extreme rainfall events - Yiqun Han; Xiao-long Wu; Qing Liu; Ruijun Wang; Lei Cao (Urban Climate, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

Pollution accumulation, sources, and risk assessment of potentially toxic elements in the soil-walnut system: insights from over 50 years of wastewater irrigation in a lead/zinc smelting region - Rongchang Zhao; Xiang Ning; Song Long; Yinwen Dong; Liang He; Wenbo Wang; Yue Gao; Chengpeng Sun; Xueyi Wang; Ruijun Miao; Shengli Wang (Environmental Geochemistry and Health, 2026)

Transition from grazing to indoor feeding elevates the risks of antibiotic resistance gene transmission in Tibetan sheep - Ze Cao; Huanyu Gong; Kairi Yang; Ting Wei; Huilin Qin; Ruijun Long; Jianwei Zhou; Jiandui Mi (Journal of Cleaner Production, 2026)

Rodent Bioturbation Significantly Enhances Annual Methane Uptake by Tibetan Alpine Grasslands - Dezhao Gan; Dongsheng Yu; Hongchao Zuo; Zheng Li; Zelong Zhang; Huinan Li; Zhenrong Lin; Hui Wang; Qingping Zhou; Jinsong Wang; Shuli Niu; Ruijun Long; et al. (Global Change Biology, 2025)
Tibetan alpine grasslands (AG) serve as critical methane (CH 4 ) sinks, yet face degradation from anthropogenic and climatic disturbances that promote subterranean rodents (e.g., Plateau zokor [ Myospalax baileyi ] and pika [ Ochotona curzoniae ]) activities. Although rodent bioturbation (e.g., burrowing, foraging and excreting) alters soil structure, soil physico‐chemical properties and productivity from AG, its impacts on CH 4 uptake remain poorly understood. Among the first, we combined paired year‐round CH 4 flux measurements from Plateau zokor mounds (ZM) and surrounding healthy meadow (HM) patches in Tibetan alpine meadow with collated CH 4 fluxes from meta‐ and synthetic analyses across Tibetan AG, temperate grasslands (TG) and tropical grasslands (TrG) globally. We observed that rodent bioturbation significantly ( p 4 uptake (HM: −0.91 ± 0.08 kg C ha −1 vs. ZM: −1.80 ± 0.19 kg C ha −1 , mean ± standard error, negative values indicate uptake). Notably, 67% of this net increase (−0.89 ± 0.10 kg C ha −1 year −1 ) due to rodent bioturbation occurred during the growing season. Meta‐analysis results revealed this phenomenon associated with significantly ( p pmoA for methanotrophs. Non‐growing season (NGS) CH 4 uptake contributed 45% and 39% to annual CH 4 uptake for HM and ZM, respectively, falling into the ranges of 12%–64% NGS CH 4 uptake contributions from TG to AG of China. The TrG showed significant ( p 4 uptake than TG and AG globally, due to the fact that significant ( p 4 flux changes and highlight soil moisture as a key driver for global CH 4 sink variations. These results emphasise the need for long‐term monitoring to better assess the ecological consequences of bioturbation in climate‐sensitive alpine ecosystems.

An integrated evaluation of potentially toxic elements and microplastics in the highland soils of the northeastern Qinghai-Tibetan Plateau - Apurva Kakade; Qunying Zhang; Tao Wu; Xin Yang; Jiandui Mi; Xiaoping Jing; Ruijun Long (Journal of Hazardous Materials, 2025)

Towards end-to-end rice row detection in paddy fields exploiting two-pathway instance segmentation - Zhiying Chen; Yinghu Cai; Yaxin Liu; Zhanpeng Liang; Hao Chen; Ruijun Ma; Long Qi (Computers and Electronics in Agriculture, 2025)

Seed dispersal and germination by yak gut passage in an alpine meadow community on the Qinghai-Tibetan Plateau - Guohua Ren; Bin Deng; Yupeng Wang; Ruijun Long (Community Ecology, 2025)

CSWin-MBConv: A dual-network fusing CNN and Transformer for weed recognition - Jinrong Cui; Youliu Zhang; Hao Chen; Yaoxuan Zhang; Hao Cai; Yu Jiang; Ruijun Ma; Long Qi (European Journal of Agronomy, 2025)

Feeding systems change yak meat quality and flavor in cold season - Qunying Zhang; Jianxin Jiao; Zhiwei Zhao; Zhiyuan Ma; Apurva Kakade; Xiaoping Jing; Jiandui Mi; Ruijun Long (Food Research International, 2025)

Microplastics in the World Oceans and Strategies for Their Control - Apurva Kakade; Jiandui Mi; Ruijun Long (Reviews of Environmental Contamination and Toxicology, 2024)

PosNet: Estimating lettuce fresh weight in plant factory based on oblique image - Jianwei Tan; Junwei Hou; Wenyu Xu; Hong Zheng; Song Gu; Yuhao Zhou; Long Qi; Ruijun Ma (Computers and Electronics in Agriculture, 2023)

Real-time missing seedling counting in paddy fields based on lightweight network and tracking-by-detection algorithm - Jinrong Cui; Hong Zheng; Zhiwei Zeng; Yuling Yang; Ruijun Ma; Yuyuan Tian; Jianwei Tan; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2023)

Effect of grazing exclusion on emission of greenhouse gases and soil organic carbon turnover in alpine shrub meadow - Zhiqiang Dang; Na Guo; Shanshan Li; A. Allan Degen; Jingjuan Cao; Bin Deng; Aidong Wang; Zhen Peng; Luming Ding; Ruijun Long; Zhanhuan Shang (Science of The Total Environment, 2023)

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Importance of Functional Ingredients in Yak Milk-Derived Food on Health of Tibetan Nomads Living Under High-Altitude Stress: A Review - Xusheng Guo; Ruijun Long; Michael Kreuzer; Luming Ding; Zhanhuan Shang; Ying Zhang; Yang Yang; Guangxin Cui (Critical Reviews in Food Science and Nutrition, 2014)

Reducing methane emissions and the methanogen population in the rumen of Tibetan sheep by dietary supplementation with coconut oil - Xuezhi Ding; Ruijun Long; Qian Zhang; Xiaodan Huang; Xusheng Guo; Jiandui Mi (Tropical Animal Health and Production, 2012)

Effects of cultivation and abandonment on soil carbon content of subalpine meadows, northwest China - Zhanhuan Shang; Jingjuan Cao; Ruiying Guo; Ruijun Long (Journal of Soils and Sediments, 2012)

Fertilization and litter effects on the functional group biomass, species diversity of plants, microbial biomass, and enzyme activity of two alpine meadow communities - Changting Wang; Ruijun Long; Qilan Wang; Wei Liu; Zengchun Jing; Li Zhang (Plant and Soil, 2010)

Establishment of Elymus natans improves soil quality of a heavily degraded alpine meadow in Qinghai-Tibetan Plateau, China - Ruizhang Feng; Ruijun Long; Zhanhuan Shang; Yushou Ma; Shikui Dong; Yanlong Wang (Plant and Soil, 2010)

Nitrous oxide emissions from two alpine meadows in the Qinghai–Tibetan Plateau - Yangong Du; Yingguang Cui; Xingliang Xu; Dongying Liang; Ruijun Long; Guangmin Cao (Plant and Soil, 2008)